2017
DOI: 10.1097/cej.0000000000000350
|View full text |Cite
|
Sign up to set email alerts
|

Parental alcohol consumption and risk of leukemia in the offspring: a systematic review and meta-analysis

Abstract: Parental alcohol consumption before and during pregnancy has been linked to adverse outcomes in the offspring including leukemogenesis. We, therefore, aimed to systematically assess and quantitatively synthesize published data on the association of paternal consumption during preconception and maternal consumption during pregnancy with leukemia risk in childhood (0-14 years). Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, we searched PubMed (until February 2016) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 33 publications
2
18
0
2
Order By: Relevance
“…Moreover, the numbers in the extreme parental age discordant cells were rather limited to allow firm conclusions on the seemingly higher contribution of the advanced paternal compared to the maternal age on ALL risk. Lastly, information on genetic markers and maternal risk factors such as alcohol consumption [33] or maternal diabetes [34] was not currently contributed by the majority of studies to further enlighten underlying pathophysiological mechanisms. Similarly, information on breastfeeding, a proposed protective factor against childhood ALL [35] was actually missing in 3 out of 5 NCC studies, thus precluding meaningful analyses; nevertheless, sensitivity analyses restricted to studies availing this information showed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the numbers in the extreme parental age discordant cells were rather limited to allow firm conclusions on the seemingly higher contribution of the advanced paternal compared to the maternal age on ALL risk. Lastly, information on genetic markers and maternal risk factors such as alcohol consumption [33] or maternal diabetes [34] was not currently contributed by the majority of studies to further enlighten underlying pathophysiological mechanisms. Similarly, information on breastfeeding, a proposed protective factor against childhood ALL [35] was actually missing in 3 out of 5 NCC studies, thus precluding meaningful analyses; nevertheless, sensitivity analyses restricted to studies availing this information showed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…95). The associations with maternal alcohol use (65) and smoking during pregnancy and ALL overall are null (80).…”
Section: Analytic Epidemiology Of Allmentioning
confidence: 99%
“…Various in utero and early childhood exposures have been investigated in the aetiology of childhood ALL [9, 10]. These include breast feeding [11], infection history [12], childcare/day care attendance [11, 12], maternal smoking [13, 14], alcohol [15, 16], caffeine [15, 17], folic acid [18, 19], iron [20], radiation [8], household paints [21], chemicals [22], pesticides [23, 24], and herbicides [25]. The weight of supporting evidence for the role of each exposure in the aetiology of childhood ALL varies.…”
Section: Introductionmentioning
confidence: 99%